Eficácia e segurança da terapia de indução da puberdade em pacientes do sexo feminino com Síndrome de Prader-Willi - Aragão, Luciana Felipe Férrer (2024)
Prader-Willi Syndrome (PWS) is a genetic disorder characterized by hypothalamic-pituitary deficiencies, including hypogonadism. The presence of hypogonadism can lead to altered body composition, insufficient uterine development, reduced bone mineral density, increased cardiovascular risk, and worse psychosocial adaptation. There is no consensus on puberty induction in girls with PWS. A study with an appropriate description of puberty induction could significantly help them. This study aimed to evaluate the effectiveness and safety of puberty induction therapy in female patients with PWS. It was an open, multicenter clinical trial conducted at the Pediatric Endocrinology Services of the Complex Hospital of the Federal University of Ceará/Ebserh and the Child Institute of the Hospital das Clínicas of the Faculty of Medicine of the University of São Paulo. The study included girls diagnosed with PWS, aged at least 12 years, with absence of thelarche or non-progressive pubertal maturation or without regular menstrual cycles. The patients were divided into a treated group with puberty induction therapy and an untreated group. The analysis was performed through physical examination, laboratory tests, imaging studies, and psychiatric evaluation. Eleven patients were included, with seven in the treated group and four in the untreated group, with average ages at the start of the protocol of 19.2 and 15.8 years, respectively. The average age of the onset of thelarche was 10.7 years, but the patients showed delayed or absent pubertal progression. The treated group exhibited satisfactory development of secondary sexual characteristics, which was not observed in the untreated group. All patients who received treatment completed puberty induction in an average time of 11.2 months. In the treated group, adequate uterine growth was observed over time, with an initial volume of 18 cm³ and a final volume of 30 cm³. In contrast, the untreated group had a uterine volume of 11 cm³ at the beginning and 12 cm³ at the end. Bone densitometry showed an improvement in the lumbar spine z-score (increase of 0.95 SDS) and total body (increase of 1.14 SDS) throughout the study in the treated group. This was the first open intervention study with hormone replacement therapy, with a comparative group, in girls with PWS, with an appropriate description of puberty induction, regarding dosage, duration, benefits, and associated risks. The study demonstrated the beneficial effect of the proposed puberty induction therapy in girls with PWS, through appropriate development of sexual characteristics, uterine growth, and bone mineral density. Furthermore, it showed the safety of this treatment during the study period.